2022
DOI: 10.3390/polym14102107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Disinfection and Steam Sterilization on the Mechanical Properties of 3D SLA- and DLP-Printed Surgical Guides for Orthodontic Implant Placement

Abstract: Three-dimensional printed surgical guides increase the precision of orthodontic mini-implant placement. The purpose of this research was to investigate the effects of disinfection and of two types of autoclave sterilization on the mechanical properties of 3D printed surgical guides obtained via the SLA (stereolithography) and DLP (digital light processing) printing methods. A total of 96 standard specimens (48 SLA and 48 DLP) were printed to analyze the tensile and flexural properties of the materials. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
2
16
1
Order By: Relevance
“…Most recently, Pop et al conducted a similar study on the influence of disinfection and autoclaving on the flexural properties of surgical guide materials for additive manufacturing [29]. In contrast to our results, they found significantly increased flexural moduli for both autoclaving cycles that the specimens were subjected to (i.e., 121 • C, 1 bar, 20 min and 134 • C, 2 bar, 10 min).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Most recently, Pop et al conducted a similar study on the influence of disinfection and autoclaving on the flexural properties of surgical guide materials for additive manufacturing [29]. In contrast to our results, they found significantly increased flexural moduli for both autoclaving cycles that the specimens were subjected to (i.e., 121 • C, 1 bar, 20 min and 134 • C, 2 bar, 10 min).…”
Section: Discussioncontrasting
confidence: 96%
“…Reasons for the contrasting results could be different post-curing conditions of the specimens, different materials, different loading speed (i.e., 5 mm/s), and possibly different specimen geometry, which, however, remained unspecified. Interestingly, one of the two materials that were examined in their study was used in the present study in group 3 (i.e., Dental SG, Formlabs Inc.), which was the only group that we found to have an increased flexural modulus after being treated at 134 • C, in agreement with the results of Pop et al [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Steam sterilization might not only cause geometric and dimensional changes, as investigated in the current study, but it might also have an effect on mechanical properties. A recent study by Pop et al investigated the effects of disinfection and steam sterilization (at 121 • and at 134 • ) on the mechanical properties of 3D-printing materials and 3D-printed surgical guides for orthodontic mini-implants [41]. The first part of the study, which investigated the mechanical properties, concluded that DLP 3D-printed specimens that underwent steam sterilization at 121 • showed a significant increase in flexural strength, the flexural modulus of elasticity, tensile strength and the tensile modulus of elasticity in comparison to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is adopted for massive production of automotive parts by Desktop Metal and is exploited for large scale fabrication of medical devices, soft actuators, and shoe soles by global corporations such as Medtronic, Boston Scientific, and Adidas, respectively. [3][4][5][6] The emerging applications of DLP printing include fabrication of biomedical implants, [7] dental surgical guides, [8] tissue models, [9][10][11] as well as wax models in jewelry, [12] sculptures in aesthetics, [13] and metamaterials in soft robotics. [14][15][16] The DLP technique is based on local photocrosslinking of a liquid ink, which mainly consists of monomers/oligomers/macromonomers, a crosslinker, and a photoinitiator.…”
Section: Introductionmentioning
confidence: 99%